ІНФОРМАЦІЙНІ ВІЙНИ (КОНФЛІКТИ): ТЕОРЕТИКО-ПРАВОВИЙ АСПЕКТ - Cherevatіuk, Victoria; Boiko, Oleksiy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Objective: in the conditions of rapid development of society, technologies and means of reproduction of information, the problem of counteraction to information war is acute. In the article, the authors draw parallels between the usual war and information warfare, in particular, identify differences between these phenomena. The aim of the article is to study the theoretical aspects of information wars (conflicts), to generalize proposals for combating information wars. Methods: the methodological basis of the study were general scientific methods of cognition, comparative law; sociological; logical; dialectical. Results: the main methods of information warfare are analyzed, in particular: bribery; blackmail; intimidation; manipulation of people’s consciousness; deterioration of the political and economic situation inside the country; creation of a fictitious opposition; kidnapping; organization and carrying out of terrorist acts, etc. It is proved that the creation of counter-propaganda; development of mass media; creation of an information coalition; development of analytical thinking in the citizens of the country, etc. are effective methods of counteracting information wars. Discussion: in this article, the authors develop the idea that we should oppose the latest information weapons to image diplomacy, promotion of the Ukrainian brand in the world and effective policies that should be implemented through various channels and means of communication in the international arena. Public diplomacy is also a tool to counter hybrid threats, misinformation and fakes. The formation of a positive image of Ukraine in the world requires close coordination with all relevant institutions, both state and non-state.